Role of Inflammatory Biomarkers in the Prevalence and Incidence of Hypertension Among HIV-Positive Participants in the START Trial. (6th September 2019) - Ghazi, Lama; Baker, Jason V; Sharma, Shweta; Jain, Mamta K; Palfreeman, Adrian; Necsoi, Coca; Murray, Daniel D; Neaton, James D; Drawz, Paul E
Abstract: BACKGROUND: The association between hypertension (HTN) and inflammatory biomarkers (interleukin-6 [IL-6] and high-sensitivity C-reactive protein [hsCRP]) in HIV-positive persons with CD4+ count >500 cells/mm 3 is unknown. METHODS: We studied HTN in participants of the Strategic Timing of AntiRetroviral Treatment (START) trial of immediate vs. deferred antiretroviral therapy (ART) in HIV-positive, ART naive adults with CD4 + count > 500 cells/mm 3 . HTN was defined as having a systolic blood pressure (BP) ≥140 mmHg, a diastolic BP ≥90 mmHg, or using BP-lowering therapy. Logistic and discrete Cox regression models were used to study the association between baseline biomarker levels with prevalent and incident HTN. RESULTS: Among 4, 249 participants with no history of cardiovascular disease, the median age was 36 years, 55% were nonwhite, and the prevalence of HTN at baseline was 18.9%. After adjustment for race, age, gender, body mass index (BMI), diabetes, smoking, HIV RNA and CD4 + levels, associations of IL-6 and hsCRP with HTN prevalence were not significant (OR per twofold higher:1.10, 95% confidence interval [CI]: 0.99, 1.20 for IL-6 and 1.05, 95% CI: 0.99, 1.10 for hsCRP). Overall incidence of HTN was 6.8 cases/100 person years. In similarly adjusted models, neither IL-6 (Hazard ratios [HR] per twofold higher IL-6 levels: 0.97, 95% CI: 0.88, 1.08) nor hsCRP (HR per twofold higher hsCRP levels: 0.97, 95% CI: 0.92, 1.02) were associated with risk of incident HTN. Associations did not differ by treatment group. Age, race, gender, and BMI were significantly associated with both the prevalence and incidence of HTN. CONCLUSIONS: Traditional risk factors and not baseline levels of IL-6 or hsCRP were associated with the prevalence and incidence of HTN in START.